2019
DOI: 10.3390/min9110707
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbon Binder for Cemented Paste Backfill: Flowability, Strength and Leaching Characteristics

Abstract: Blast furnace slag was used as the main raw material to prepare the alkali activated slag (AAS), a low-carbon binder, for cemented paste backfill (CPB). The optimum parameters for preparing the AAS binders using an orthogonal experiment were obtained. Under the optimum conditions (NaOH content was 3 wt. %, Ordinary Portland cement (OPC) content was 7 wt. %, and gypsum dosage was 4 wt. %), the 28 days compressive strength of the binder was 29.55 MPa. The flow ability of the fresh CPB slurry decreased with solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 64 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…On the one hand, because of the increase in solid content, the distance between the aggregate particles of the CPB mixture is reduced. In the slump test, the sliding between aggregate particles is more likely to generate friction, and the fluidity deteriorates, thereby reducing the slump value [15,28]. On the other hand, an increase in solid content leads to an increase in the consistency of the CPB slurry, a decrease in fluidity, and a decrease in the slump value [29].…”
Section: Effect Of Response Surface Parameters On the Slump Of The Cpmentioning
confidence: 99%
“…On the one hand, because of the increase in solid content, the distance between the aggregate particles of the CPB mixture is reduced. In the slump test, the sliding between aggregate particles is more likely to generate friction, and the fluidity deteriorates, thereby reducing the slump value [15,28]. On the other hand, an increase in solid content leads to an increase in the consistency of the CPB slurry, a decrease in fluidity, and a decrease in the slump value [29].…”
Section: Effect Of Response Surface Parameters On the Slump Of The Cpmentioning
confidence: 99%
“…Mining, as a traditional heavy industry, provides raw material support for national economic development [1,2], but also inevitably brings a negative impact on the environment [3][4][5]. In the 1980s, with the development of cemented paste backfill (CPB), tailings were used in large quantities for the preparation of high concentration backfill slurry and were recycled [6,7]. Meanwhile, CPB has gradually become a current research hotspot because of its excellent performance in controlling surface settlement, consuming mine solid waste, and backfill underground mining areas, which fits in with the theme of green development [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Alkali-activated binders could be designed to have superior properties compared to cement, namely the development of earlier and higher mechanical strengths [22], better resistance to acids and sulphates [23], and lower heat of cement hydration [24]. Numerous studies [17,18,[25][26][27] have been recently shown to better assess the mechanical, workability and microstructural properties of CPB materials by using alkali-activated slag (AAS) as a binder. These studies have shown that, compared to those made up of OPC, CPB samples containing AAS as binder were found to produce remarkably higher early-age strength and stability.…”
Section: Introductionmentioning
confidence: 99%